Desain Pengembangan Bahan Ajar Digital Berbantuan Aplikasi Animaker Pada Mata Kuliah Pendidikan TIK (Teknologi Informasi dan Komunikasi) - Faiz Fauzan Muhajir; Budi Tjahjono; Badri Munawar (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
This research aims to see the effectiveness of the use of teaching material development. digitally assisted Animaker application for STKIP student Sheikh Manshur who took ICT Education courses The use of animation in the learning process is to enrich the creativity of students in the era of learning. Technology. The problem that occurs in the education process at STKIP Syekh Manshur is the lack of access. to operate digital-based teaching materials, although there are already available facilities such as laptops or a projector. the learning process carried out in ICT education in blanded play with learning using animated videos will make it easier for Students Enriching teaching materials. Researchers use the ADDIE (Analysis, Design, Develop, Implementation, and Evaluation). The research subjects were 30 STKIP Students sheikh Manshur who took ICT Education Courses The results of the research conducted at the Evaluation stage showed The success of 85.2% can be categorized as very high. Digital teaching materials Using the help of animaker application is considered effective for use by STKIP student Syekh Manshur